Cedera Ginjal Akut Pasca Ginjal Ec. Djenkolisme - Ris Nandar; Amelia Nasti (LPPM Universitas Abdurrab, 2023)
Djenkolism is one of the causes of acute kidney Injury. The causes of djengkolism is djenkolic acid which is contained in djenkol bean (Archidendron pauciflorum). This case usually occurs in Southeast Asia especially Indonesia, where this plant is grown and consumed. Djengkolism can cause various clinical manifestasions such as abdominal colic, renal colic, urinary tract obstruction and even acute kidney injury.